Role of methionine in bacterial chemotaxis: requirement for tumbling and involvement in information processing. - Springer, M S (1975)
Chemotactic responses are mediated by modulation of the frequency of tumbling. Studies with methionine auxotrophs of wild-type Escherichia coli and four mutants which tumble continuously show that methionine or one of its metabolites is involved in the tumbling process. Following removal of methionine, the wild type and two mutants, after various periods of time, became unable to tumble. The presence of constant levels of chemical attractants considerably shortened these periods in the three strains and eliminated tumbling in another mutant. This effect of attractants considerably shortened these periods in the three strains and eliminated tumbling in another mutant. This effect of attractants implies that methionine or some derivative of methionine is also involved in transducing chemical stimuli to bacterial responses.